Table of Content - - (Journal of Islamic Sciences, 2024)
Table of Content:1. The relationship of the science of jurisprudence with theology - jurisprudence and jurisprudence rulesDr. Jarallah Abdullah Ahmed Aljarallah2. Irrevocable divorce, BaynunahSoghra, before Sharia courts inside the Green Line(An analytical study)Dr. Mohammed Saeed Zahra, Dr. Abdullah Jamil Abu Wahdan3. Climate Change and Legal Responsibility: Challenges and Solutions from the Perspective  of Environmental JurisprudenceMrs. Muna Ateeq Rubayea Aldarmaki4. Conditions of Comprehensiveness and Distinction in Juristic DefinitionsMrs. Amal Tariq Al-Omar
Keywords: Journal of Islamic Sciences